Characterization of an extrapolation chamber as a primary standard dosimeter for beta radiation - Reynaldo, S. R.; Benavente, J. A.; Da Silva, T. A. (Scientia Plena, 2013)
Inbeta or electron radiation fields, operational dose equivalent quantities, based on absorbed dose in tissue, are used for radiation protection of the workers. Low penetration and high scattering in matter are characteristics of beta radiation that make its dosimetry more complex. Reliable measurements of absorbed dose in tissue must be traceable to an extrapolation chamber, which is the only primary standard dosimeter available for beta radiation. This ionization chamber uses the extrapolation to zero volume as the method of measurement of absorbed doses in 0.07 mm of tissue, DT(0.07);its requires the determination of correction factorsrelated to influences from the detector itself and from the radiation field geometry. In this work, a 23392 model PTW extrapolation chamber was characterized by determining its collector electrode area, its true-null depth and the influence in its response of temperature, humidity and chamber depth. Values of the true-null depth were 0.46±0.04 mm and 0.40±0.04 mm for 90Sr/90Y and 85Kr beta field sources, respectively. Corrections of the chamber ionization current, according to the ideal gas law significantly reduced the high influence of temperature; air humidity influence showed to be negligible within the 50% to 70% range. The high dependence of the chamber response with its volume addressed the need to determine accurately its true-null depth. These results are to be used as appropriate corrections for accurate absorbed dose in tissue determination.